PERTANGGUNGJAWABAN PIDANA TERHADAP PENGGUNA IJAZAH PALSU OLEH ANGGOTA DPRD DALAM PEMILIHAN UMUM LEGISLATIF (CONTOH KASUS PUTUSAN NOMOR: 196 K/PID.SUS/2016) - Hery Firmansyah; Imelda Yohana Dewi (Faculty of Law - Tarumanagara University, 2019)
A diploma is usually used as one of the conditions to meet the requirements for registration or recruitment from a position. For example, for the nomination of legislative members to be members of the DPR, DPD, Provincial DPRD and Regency DPRD. However, most legislative candidates in the regions do not have genuine diplomas for certain reasons, eventually the legislative candidates use fake diplomas in order to qualify in the general election. The problem studied is how criminal accountability of fake diploma users by DPRD members in legislative elections (Case Example Decision Number: 196 K / Pid.Sus / 2016)? The research method that I use is a normative legal research method which is also supported by interview data. The author analyzes that criminal liability is adjusted to the condition that a person can be held accountable based on criminal acts committed and articles used where the sanctions are there, in this case the article imposed is Article 69 paragraph (1) of the Law on the National Education System. When viewed from a decision that is used as an example by referring to its legal considerations, a court judge has considered everything so that he can be held to hold criminal responsibility and the judge has the right to decide. The author advises to conduct socialization so that there is no indication of the use of fake diplomas, it is necessary to impose a severe sentence for each actor, and the legislative candidates to be honest in nominating themselves as representatives of the people.